High-entropy heat insulation aerogel material and preparation method thereof
By inducing high-entropy metal oxide growth in graphene oxide aerogels, high-entropy thermal insulation aerogels with low thermal conductivity and high compression elasticity were prepared, solving the failure of traditional materials at high temperatures and the separation of high-entropy ceramic phases at high temperatures. The problem of this achieves excellent thermal insulation performance at room temperature and high temperature.
Patent Information
- Application Number
- CN202411699003.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Traditional polymers and ceramic thermally insulated aerogels fail in high temperature environments. High-entropy ceramic materials are phase separation due to large differences in atomic radius, making it difficult to exert the lattice distortion effect of solid-solution alloys, affecting the thermal insulation performance.
By sequestering the multi-metal inorganic salts with oxygen-containing functional groups in the aerogel wall of graphene oxide, the high-entropy metal oxide crystal growth is induced by using the graphene three-dimensional network skeleton to prepare the pore walls from two-dimensional layered mesoporous high-entropy metal oxidation. Aerogel material with overlapping substances realizes the preparation of high-entropy thermally insulated aerogels.
The prepared high-entropy thermal insulation aerogel has good thermal insulation performance at room temperature and high temperature, low thermal conductivity, good compression elasticity, stable existence, significantly better than single-component oxide aerogel, and is suitable for high-temperature zone isolation. hot.
Smart Images

Figure CN119284958A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a high entropy thermal insulation aerogel material and a preparation method thereof. Background Art
[0002] High-performance thermal insulation materials are key components for thermal protection in aerospace, industrial storage tanks, pipelines, and military industries, as well as key materials for energy-saving buildings and rail transit. The unique high-porosity structure of aerogel materials can effectively reduce solid-state heat conduction. At the same time, due to its advantages such as low density, high specific surface area, and thermal stability, it has become a thermal insulation material with excellent performance.
[0003] However, traditional polymer thermal insulation aerogels such as polystyrene foam, polyurethane foam, rock wool, etc. can only be used at room temperature. Ceramic thermal insulation aerogels can have excellent thermal insulation properties within a certain wide temperature range.
[0004] For example, silica aerogel can be used at room temperature to 600°C, but it is generally prepared using an organic precursor through a sol-gel method combined with supercritical drying. The preparation process is complex, it only has a single component, and the prepared silica nanoparticles are overlapped by a beaded structure with poor mechanical compressibility. The structure collapses in an environment above 600°C, and cannot meet the growing demand for thermal insulation in high-temperature areas.
[0005] In recent years, entropy-stabilized oxide materials have gradually emerged. High-entropy ceramics usually contain five or more ceramic powder components, with similar contents of each component, high configurational entropy, and lattice distortion caused by the entropy effect can reduce the thermal conductivity of ceramics. At the same time, they have higher strength, modulus, and hardness than traditional ceramics. They also have strong covalent bond characteristics and high melting points. They can be used in various extreme service environments and are an important development direction for the new generation of thermal structural materials. For high-entropy alloys, the greater the difference in atomic radius, the more serious the lattice distortion, thereby increasing the refractive index of phonons and further improving the thermal insulation performance. However, based on the Hume-Rothery rule, when the difference in atomic size is too large, due to the positive heat of reaction, its direct alloying and the corresponding macroscopic material preparation are very difficult. This type of high-entropy composition is more prone to phase separation, and it is difficult to exert the lattice distortion effect of solid solution alloys, thus affecting the thermal insulation performance. Summary of the invention
[0006] In order to solve the above technical defects, the present invention proposes a method for preparing high-entropy thermal insulation aerogel, and successfully prepares a high-entropy oxide aerogel composed of elemental components that are immiscible with each other and have a large difference in atomic radius.
[0007] The present invention uses a precursor multi-metal inorganic salt component as an ion source to chelate with oxygen-containing functional groups in the graphene oxide aerogel wall into the interlayer, uses the three-dimensional network skeleton of the graphene aerogel as a sacrificial template, and utilizes the template induction effect of two-dimensional graphene sheets on the growth of high-entropy metal oxide crystals to prepare an aerogel material with a continuous network whose pore walls are overlapped by two-dimensional layered mesoporous high-entropy metal oxides. The prepared high-entropy insulating aerogel has good thermal insulation properties both at room temperature and at high temperature.
[0008] One of the technical solutions of the present invention is to provide a method for preparing a high entropy thermal insulation aerogel, comprising the following steps: (1) coating a graphene oxide dispersion liquid into a film and drying it to obtain a graphene oxide film; (2) Soaking the obtained film in an aqueous solution of a multi-metal inorganic salt for 4-12 hours, and drying to obtain a multi-metal ion hybrid membrane; the multi-metal salt includes two or more metal elements that are not mutually soluble; such as zirconium and lanthanum, copper and tantalum, molybdenum and silver, molybdenum and copper, niobium and copper, copper and tungsten, zirconium and copper, copper and iron, copper and cobalt, copper and hafnium, etc.
[0009] (3) placing the obtained multi-metal ion hybrid membrane in a foaming agent for foaming, and drying to obtain a multi-metal ion hybrid aerogel; (4) The obtained multi-metal ion hybrid aerogel is heat-treated in an inert gas to obtain a high entropy metal oxide and graphene composite aerogel, and then the composite aerogel is heat-treated in air to remove the graphene template to obtain a high entropy metal oxide aerogel.
[0010] Furthermore, the graphene oxide film in step 1 has a thickness of 10-100 μm.
[0011] Furthermore, the multi-metal inorganic salt in step 2 includes all metal inorganic salts, and the concentration of the aqueous solution is not less than 10wt%.
[0012] Furthermore, the foaming agent in step 3 is one of hydrazine hydrate solution, sodium borohydride solution, sodium bicarbonate solution and sodium carbonate solution.
[0013] Furthermore, the heat treatment in the inert gas in step 4 is maintained at 1200° C. for 2-4 hours, and the heat treatment in the air in step 4 is maintained at 600° C. for 1-2 hours.
[0014] The high-entropy oxide aerogel prepared by this scheme has low thermal conductivity and low density, good compression elasticity at room temperature and high-temperature air environments, high elasticity and stable existence in high-temperature air. The thermal insulation performance is significantly better than the corresponding single-component oxide aerogel material, and it has good application prospects in the fields of thermal insulation and high temperature resistance.
[0015] The second technical solution of the present invention is to provide a high entropy thermal insulation aerogel prepared by the above method, wherein the high entropy thermal insulation aerogel has a spherical microporous structure, and the pore walls are overlapped by two-dimensional layered mesoporous high entropy metal oxides.
[0016] The introduction of high entropy effect in aerogel causes serious distortion in the lattice structure and a large number of grain boundaries cause a large amount of phonon scattering. By changing the different metal ions in the high entropy ceramic, preferably elements with large differences in atomic radius and atomic mass, the mass field disturbance of phonon scattering in the high entropy ceramic can be increased, thereby hindering phonon transmission, which can effectively reduce the thermal conductivity of solid thermal conduction ceramics in the aerogel wall.
[0017] In addition, the surface of the two-dimensional high-entropy metal oxide sheet contains a large number of mesopores, which can further reduce the mean free path of phonons and gas heat conduction. And the high-entropy ceramics grown on the spherical surface structure will introduce a large curvature stress field to the high-entropy crystal, thereby increasing the stress field disturbance of phonon scattering in the high-entropy ceramics, further hindering phonon transmission and reducing the thermal conductivity of the high-entropy ceramics.
[0018] The third technical solution of the present invention is to provide thermal insulation application of the above-mentioned high entropy thermal insulation aerogel.
[0019] Beneficial effects of the present invention: (1) The problem that when the atomic size difference is too large, the high entropy composition is prone to phase separation and it is difficult to exert the solid solution lattice distortion effect has been solved.
[0020] (2) Through a simple solution immersion method, a variety of metal inorganic salt ions were anchored on the two-dimensional graphene oxide sheet, and high-entropy oxide aerogels composed of elemental components that are immiscible with each other and have large differences in atomic radii were successfully prepared.
[0021] (3) The obtained high entropy aerogel material has good thermal insulation effect both at room temperature and in high temperature air environment. Its thermal conductivity is as low as 11 m W / (m•K) at room temperature. At the same time, based on the oxidation resistance of oxide ceramics, the thermal conductivity of the prepared high entropy aerogel is as low as 40 m W / (m•K) in a high temperature environment of 1000℃.
[0022] (4) The obtained high-entropy aerogel material has good compression resilience both at room temperature and in high-temperature air environments. The spherical microporous structure and two-dimensional nanoscale thin walls are used as elastic templates. Combined with the strengthening effect of the high-entropy crystals in the aerogel wall, the ability of the aerogel pore wall to resist deformation is improved, thus avoiding structural damage under high-temperature thermal stress and achieving the high elasticity of the high-entropy aerogel at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the SEM image of high entropy metal oxide aerogel.
[0024] Figure 2 This is the EDS diagram of element distribution of high entropy metal oxide aerogel. DETAILED DESCRIPTION
[0025] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.
[0026] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0027] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0028] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0029] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0030] The mesopores described in the present invention are pores with a pore diameter of 2-50 nm.
[0031] Example 1 The concentration was 10 mg / cm 3 The graphene oxide solution (purchased from Hangzhou Gaoxi Technology Co., Ltd.) was scraped and dried into a 10 μm thick film, which was then immersed in a salt solution containing copper, tungsten, molybdenum, tantalum, and niobium metal cations in equal molar ratios. The solution concentration was 40wt%, and the immersion time was 4h. After drying, it was placed in a 30% hydrazine hydrate solution for foaming for 1h to obtain a graphene oxide aerogel with a spherical continuous microporous curved surface network structure. After the above aerogel was heat-treated at 1200℃ in an inert gas for 2h, a high-entropy metal oxide graphene composite aerogel was obtained, which was then heat-treated at 600℃ in air for 1h to remove the graphene template and obtain a high-entropy solid solution metal oxide aerogel. The density of the aerogel is 16 mg / cm 3 The thermal conductivity is 15 m W / (m•K) at room temperature and 55 m W / (m•K) in air at 1000℃. When compressed 100 times with a deformation of 60% in air at 1000℃, the elastic recovery rate reaches 80%.
[0032] Example 2 The concentration was 10 mg / cm 3 The graphene oxide solution (purchased from Hangzhou Gaoxi Technology Co., Ltd.) was scraped and dried into a 100 μm thick film, which was then immersed in a salt solution containing copper, chromium, niobium, iron, and platinum metal cations in equal molar ratios. The solution concentration was 50wt%, and the immersion time was 4h. After drying, it was placed in a 30% sodium carbonate solution for foaming for 1h to obtain a graphene oxide aerogel with a spherical continuous microporous curved surface network structure. After the above aerogel was heat-treated at 1200℃ in an inert gas for 4h, a high-entropy metal oxide graphene composite aerogel was obtained, which was then heat-treated at 600℃ in air for 2h to remove the graphene template and obtain a high-entropy solid solution metal oxide aerogel. The density of the aerogel is 18 mg / cm 3 The thermal conductivity is 16 m W / (m•K) at room temperature and 60 m W / (m•K) in air at 1000℃. When compressed 100 times with a deformation of 60% in air at 1000℃, the elastic recovery rate reaches 78%.
[0033] Example 3 The concentration was 10 mg / cm 3 The graphene oxide solution (purchased from Hangzhou Gaoxi Technology Co., Ltd.) was scraped and dried to form a film, and then immersed in a salt solution containing silver, tungsten, titanium, rhenium, niobium, yttrium, vanadium, neodymium, iron and copper metal cations in equal molar ratios. The solution concentration was 30wt%, and the immersion time was 4h. After drying, it was placed in a 30% sodium bicarbonate solution for foaming for 1h to obtain a graphene oxide aerogel with a spherical continuous microporous curved surface network structure inside. After the above aerogel was heat-treated at 1200℃ in an inert gas for 3h, a high-entropy metal oxide graphene composite aerogel was obtained, which was then heat-treated at 600℃ in air for 2h to remove the graphene template and obtain a high-entropy solid solution metal oxide aerogel. The density of the aerogel is 12 mg / cm 3 The thermal conductivity is 11 m W / (m•K) at room temperature and 40 m W / (m•K) in air at 1000℃. When compressed 100 times with a deformation of 60% in air at 1000℃, the elastic recovery rate reaches 86%.
[0034] Example 4 The concentration was 10 mg / cm 3The graphene oxide solution (purchased from Hangzhou Gaoxi Technology Co., Ltd.) was scraped and dried to form a film, and then immersed in a salt solution containing nickel, zirconium, chromium, manganese, iron, cobalt, hafnium, copper, zinc and praseodymium metal cations in equal molar ratios. The solution concentration was 50wt%, and the immersion time was 4h. After drying, it was placed in a 30% sodium borohydride solution for foaming for 1h to obtain a graphene oxide aerogel with a spherical continuous microporous curved surface network structure inside. After the above aerogel was heat-treated at 1200℃ in an inert gas for 2h, a high-entropy metal oxide graphene composite aerogel was obtained, which was then heat-treated at 600℃ in air for 1h to remove the graphene template, and a high-entropy solid solution metal oxide aerogel was obtained. Its element distribution is as follows Figure 2 As shown. The density of the aerogel is 20 mg / cm 3 The thermal conductivity is 19 m W / (m•K) at room temperature and 70 m W / (m•K) in air at 1000℃. When compressed 100 times at a deformation of 60% in air at 1000℃, the elastic recovery rate reaches 81%.
[0035] Comparative Example 1 The concentration was 10 mg / cm 3 The graphene oxide solution (purchased from Hangzhou Gaoxi Technology Co., Ltd.) was scraped and dried into a 10 μm thick film, which was then immersed in a salt solution containing only zirconium ions. The solution concentration was 60wt% and the immersion time was 4h. After drying, it was placed in a 30% hydrazine hydrate solution for foaming for 1h to obtain a graphene oxide aerogel with a spherical continuous microporous curved surface network structure. After the above aerogel was heat-treated at 1200℃ in an inert gas for 3h, a zirconium oxide graphene composite aerogel was obtained, which was then heat-treated at 600℃ in air for 1h to remove the graphene template to obtain a zirconium oxide aerogel. The density of the aerogel is 13 mg / cm 3 The thermal conductivity is 26 mW / (m•K) at room temperature, 120 mW / (m•K) in air at 1000℃, and the elastic recovery rate is 30% when compressed 100 times at 60% deformation in air at 1000℃.
[0036] Comparative Example 2 The concentration was 10 mg / cm 3The graphene oxide solution (purchased from Hangzhou Gaoxi Technology Co., Ltd.) was scraped and dried into a 10 μm thick film, which was then immersed in a salt solution containing zirconium, titanium, tantalum, niobium, and hafnium metal cations with a solution concentration of 5wt% and an immersion time of 4h. After drying, it was placed in a 30% hydrazine hydrate solution for foaming for 1h to obtain a graphene oxide aerogel with a spherical continuous microporous curved surface network structure. After the above aerogel was heat-treated at 1200℃ in an inert gas for 2h, a high entropy metal oxide graphene composite aerogel was obtained, which was then heat-treated at 600℃ in air for 1h to remove the graphene template, and the structure collapsed. Due to the low oxide content, the macroscopic structure of the aerogel could not be obtained.
[0037] Comparative Example 3 Metal particles of nickel, zirconium, chromium, manganese, iron, cobalt, hafnium, copper, zinc and praseodymium are mixed in an equal molar ratio, and a block is prepared by high pressure and high temperature sintering. The obtained block has a phase-separated crystal structure.
[0038] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.
Claims
1. A method for preparing a high entropy thermal insulation aerogel, characterized in that: The following steps are involved: (1) coating a graphene oxide dispersion liquid into a film and drying it to obtain a graphene oxide film; (2) soaking the obtained film in an aqueous solution of a multi-metal inorganic salt for 4-12 hours, and drying to obtain a multi-metal ion hybrid membrane; the multi-metal salt includes two or more metal elements that are not soluble in each other; (3) placing the obtained multi-metal ion hybrid membrane in a foaming agent for foaming, and drying to obtain a multi-metal ion hybrid aerogel; (4) The obtained multi-metal ion hybrid aerogel is heat-treated in an inert gas to obtain a high entropy metal oxide and graphene composite aerogel, and then the composite aerogel is heat-treated in air to remove the graphene template to obtain a high entropy metal oxide aerogel.
2. The preparation method according to claim 1, characterized in that: The graphene oxide film in step 1 has a thickness of 10-100 μm.
3. The preparation method according to claim 1, characterized in that: The multi-metal inorganic salt in step 2 includes five or more metal inorganic salts, and the concentration of the aqueous solution is not less than 10 wt%.
4. The preparation method according to claim 1, characterized in that: The foaming agent in step 3 is one of hydrazine hydrate solution, sodium borohydride solution, sodium bicarbonate solution and sodium carbonate solution, with a concentration of 30% and a foaming time of 1 hour.
5. The preparation method according to claim 1, characterized in that: The heat treatment in the inert gas in step 4 is to maintain the temperature at 1200° C. in the inert gas for 2-4 hours, and the heat treatment in the air in step 4 is to maintain the temperature at 600° C. in the air for 1-2 hours.
6. A high entropy thermal insulation aerogel prepared by the preparation method as claimed in claim 1.
7. The high entropy thermal insulation aerogel according to claim 6, characterized in that: The pore walls are composed of two-dimensional lamellar mesoporous high-entropy metal oxide crystals.
8. A thermal insulation application of the high entropy thermal insulation aerogel as claimed in claim 1.
Citation Information
Patent Citations
Preparation methods of nanometer porous metal and nanometer porous metal and lithium-sulfur battery positive pole material
CN104600249A
Preparation method using metal ions to induce graphene three-dimensional network
CN109231186A
Preparation method of mesoporous metal oxide two-dimensional sheet with adjustable components
CN114620769A
High-elasticity graphene composite aerogel as well as preparation method and application thereof
CN115974059A
Double-negative-index ceramic aerogels for thermal superinsulation
US20220144714A1